Pemanfaatan Media Sosial (Digital Marketing) untuk Pemasaran Produk UMKM - Muljanto Silajadja; Pamela Magdalena; Trinandari Prasetyo Nugrahanti (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
For the last decade, promoting a new product has a high cost, which takes a long processing time, then the advertising must go through the phase of designing and printing. In the time being, the marketing process has a short time penetrating the newly market sharing because of social media, when Indonesia has become enormous of using social media. By exploring the phenomenon of social media as a marketing medium, this paper is aimed to provide a brief explanation of the usefulness of social media for the empowerment of the regional community. The collection of data analysis has been held in small-medium enterprises in Indonesia from 2020 until 2022 as anticipated the pandemic's effect, where the national economy has collapsed with a high probability of bankruptcy in all sectors. Considering the economic impact, all regional community has concerns with social media as a new business tool media as an innovative and creative marketing process; the fundamental motive is to keep the existing business as usual activity. All the previous research has proven that the volatile existence of a small-medium enterprise is a vital indicator of keeping a sustainable business in the long term. Then this is supported by the high dynamic pattern of demand, particularly the quick response preferences and small production capacity as a handicap for reaching the economic scale. As a comprehensive explanation, this recommendation is to push on the high government intention of fixing the empowering regulation in marketing, operational and financing activity because of the high level of weakness aspect in this sector.